The effect of simulation experience on Saudi nursing students' advance cardiac life support knowledge - Mohammed S. Aljohani; Ahmad Tubaishat; Insaf Shaban (Elsevier, 2019)
Background: Simulation has been used widely in medical education. Little is known about its uses in nursing field. Objective: This study was conducted to examine the effect of simulation-based learning experiences on the acquisition of knowledge regarding Advance Cardiac Life Support (ACLS). Methods: A quasi-experimental design with pre and post-test was used.Setting.We targeted students in one university in the City of Madinah, which is located to the west of Riyadh, the Capital of the Kingdom of Saudi Arabia. Participants: The target population was Saudi student nurses, and a convenience sample of 123 nursing students from the College of nursing within one of Government University. Results: The test results showed that there were statistically significant differences between the mean scores of pre-test and post-test, indicating that simulation has an effect on increasing the ACLS knowledge of nursing students. Conclusion: We assume that simulation experience can positively influence students' knowledge acquisition.